Xylarols A–G, structurally diverse specialized metabolites from mangrove endophytic fungus Xylaria sp. AH-75 and their anti-colorectal cancer activities - Dongmei Lin; Chengyan Chu; Falei Zhang; Xinghao Xu; Yue Li; Ziqian Liao; Xuanzheng Yue; Hanqi Zhang; Yuanyuan Feng; Huixiang Yang; Xiaolong Yang (Phytochemistry, 2026)

Genetic mechanism and geological significance of calcite veins in volcanic rocks: a case study from the Carboniferous Batamayineishan Formation, Junggar Basin - Hanqing Liu; Chunmei Dong; Chengyan Lin; Huoqing Gao; Guoqiang Luan; Lihua Ren (Carbonates and Evaporites, 2026)

Suppressed upwelling during the Cambrian–Ordovician transition revealed by coupled Cr–Cd isotope systematics - Guoqiang Luan; Karem Azmy; Robert Frei; Chengyan Lin; Jianli Lin; Guangyou Zhu (Geochimica et Cosmochimica Acta, 2026)

The geometry, kinematic and differential deformation sequence of intraplate strike-slip faults in central Tarim Basin, NW China: Implications for paleokarst reservoir distribution - Haocheng Liu; Chengyan Lin; Chunmei Dong; Guoqiang Luan; Pingshan Ma; Lihua Ren; Chunguang Shen; Baozhu Guan (Journal of Asian Earth Sciences, 2026)

Study on the release pattern of radon exhalation in the overburden soil of uranium tailings under arid climate and prediction based on Fully Connected Neural Network (FCNN)-based deep learning radon prediction model - Xianwei Wu; Yifan Chen; Dongying Lin; Shijie Fang; Le Xiao; Chengyan Yan; Yong Liu (Journal of Environmental Radioactivity, 2026)

Machine learning applications in tight porous media: Challenges, advances, and future directions - Guiang Li; Chengyan Lin; Yuqi Wu; Pengjie Ma; Pejman Tahmasebi; Chunmei Dong; Weibin Liu; Xinyu Du; Ziru Zhao (Earth-Science Reviews, 2025)

Core microbiome and microbial community characteristics of three ecological niches contribute to the growth of Leymus chinensis - Peiran Guo; Bingbing Jia; Jiaying Lin; Chengyan Lu; Tai Liu; Baihui Hao; Yiwen Xv; Qian Wang; Yvnong Chen; Wei Guo; Frank Yonghong Li (Plant and Soil, 2025)

A systematic study of pipe and electrical connections for multi-stack vanadium redox flow battery modules considering electrolyte transport delays - Shaojin Wang; Yang Li; Chengyan Li; Xifeng Lin; Wenbo Ma; Nannan Tong; Binyu Xiong (Chemical Engineering Journal, 2025)

Diagenetic fluid evolution and its implication for hydrocarbon accumulation in Ordovician carbonate of the Tazhong area, Tarim Basin: Constraints from petrology, fluid inclusions, and geochemistry of calcite cements - Haocheng Liu; Chengyan Lin; Chunmei Dong; Guoqiang Luan; Lihua Ren; Guoyin Zhang; Yintao Zhang; Baozhu Guan (Marine and Petroleum Geology, 2025)

Arbuscular mycorrhizal fungi enhance Leymus chinensis resistance to salinity predominantly through regulating root endosphere bacteria - Peiran Guo; Yazhou Hou; Bingbing Jia; Yuchen Wang; Chengyan Lu; Run Wang; Jiaying Lin; Yanan Zhang; Wei Guo; Frank Yonghong Li (Plant and Soil, 2025)

Time-Series models for ground subsidence and heave over permafrost in InSAR Processing: A comprehensive assessment and new improvement - Chengyan Fan; Cuicui Mu; Lin Liu; Tingjun Zhang; Shichao Jia; Shengdi Wang; Wen Sun; Zhuoyi Zhao (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Study on Connectivity of Fractured-Vuggy Marine Carbonate Reservoirs Based on Dynamic and Static Methods - Yintao Zhang; Chengyan Lin; Lihua Ren; Chong Sun; Jing Li; Zhicheng Wang; Guojin Xu (Journal of Marine Science and Engineering, 2025)
Fractured-vuggy marine carbonate reservoirs, as an unconventional energy resource, hold significant potential for exploration and development. In this study, the Manshen block of the Furman oilfield in the Tarim Basin, China, was selected as the research object. A systematic investigation was conducted on the types of marine carbonate reservoir bodies, production characteristics, and both static and dynamic connectivity. Static connectivity analysis was performed using the heat diffusion equation and the multi-source potential field method. Dynamic connectivity evaluation was carried out by combining the dynamic time warping (DTW) algorithm with the analytic hierarchy process (AHP). Well logging, core analysis, and cast-thin section experiments were utilized to determine the types of reservoir spaces. The results indicate that the main types of reservoir spaces in the study area are caves, pores, and fractures. The fractures are primarily structural, with secondary development of dissolution fractures, weathering fractures, and sutures. The productivity changes in oil wells in the study area are classified into three types: slow decline, rapid decline, and high-speed decline. Based on the connectivity coefficients, wells were divided into three connectivity groups, with the A32 well group having the highest connectivity, followed by B5 well group 1, and B5 well group 2 having the lowest connectivity. The research provides technical support for the accurate evaluation of marine carbonate reservoirs and contributes to enhancing the efficiency of oil and gas exploration and development.

Analysis of Microscopic Remaining Oil Based on the Fluorescence Image and Deep Learning - Yimin Zhang; Chengyan Lin; Lihua Ren (Journal of Fluorescence, 2024)

Fault system dynamics and their impact on ordovician carbonate karst reservoirs: Outcrop analogs and 3D seismic analysis in the Tabei region, Tarim Basin, NW China - Fenglei Li; Chengyan Lin; Lihua Ren; Guoyin Zhang; Yintao Zhang; Baozhu Guan (Marine and Petroleum Geology, 2024)

The joint controls of tectonism, sedimentation and diagenesis on reservoir quality in the East China Sea Basin - Wenguang Wang; Chengyan Lin; Xianguo Zhang (Marine and Petroleum Geology, 2024)

The impact of tectonic inversion on diagenesis and reservoir quality of the Oligocene fluvial sandstones: The upper Huagang formation, Xihu Depression, East China Sea Shelf Basin - Jianli Lin; Chunmei Dong; Chengyan Lin; Dongping Duan; Pengjie Ma; Ziru Zhao; Binbin Liu; Xianguo Zhang; Xin Huang (Marine and Petroleum Geology, 2024)

Marine anoxia events across the upper Cambrian (stage 10) of eastern Gondwana: Implications from paleoenvironmental geochemical proxies - Guoqiang Luan; Chengyan Lin; Karem Azmy; Liyun Fu; Chunmei Dong; Haocheng Liu; Zhaoqun Zhu; Fajie Cai (Marine and Petroleum Geology, 2024)

Evaluation of sweet spots for a tight sandstone reservoir: A quantitative study of diagenesis in the fourth member of the Oligocene Huagang Formation, Xihu Depression, East China Sea Shelf Basin - Wenguang Wang; Chengyan Lin; Xianguo Zhang (Marine and Petroleum Geology, 2024)

Corrigendum to “An end-to-end approach to predict physical properties of heterogeneous porous media: Coupling deep learning and physics-based features” [Fuel 352 (2023) 128753] - Yuqi Wu; Senyou An; Pejman Tahmasebi; Keyu Liu; Chengyan Lin; Serveh Kamrava; Chang Liu; Chenyang Yu; Tao Zhang; Shuyu Sun; Samuel Krevor; Vahid Niasar (Fuel, 2024)

Opportunity and challenges in recovering and functionalizing anode graphite from spent lithium-ion batteries: A review - Yang Gao; Shaoyan Zhang; Shuanglong Lin; Zhongqiu Li; Yongqiang Chen; Chengyan Wang (Environmental Research, 2024)

Influence of earthquake on radon exhalation law at the beach of the uranium tailing reservoir under high temperature environment - Chengyan Yan; Yong Liu; Dongyin Lin; Xingwang Dai; Le Xiao; Zhangkai Chen; Zhenghao He; Yifan Chen (Journal of Environmental Radioactivity, 2024)

Elastic rock properties analysis of diagenetic facies identification of deep tight sandstone in the Xihu Sag, China - Wenguang Wang; Chengyan Lin; Xianguo Zhang (Marine and Petroleum Geology, 2024)

An end-to-end approach to predict physical properties of heterogeneous porous media: Coupling deep learning and physics-based features - Yuqi Wu; Senyou An; Pejman Tahmasebi; Keyu Liu; Chengyan Lin; Serveh Kamrava; Chang Liu; Chenyang Yu; Tao Zhang; Shuyu Sun; Samuel Krevor; Vahid Niasar (Fuel, 2023)

IL-9-Producing Th9 Cells Participate in the Occurrence and Development of Iodine-Induced Autoimmune Thyroiditis - Yiwen Li; Hao Liu; Chengyan He; Yawen Lin; Lei Ma; Haibo Xue (Biological Trace Element Research, 2023)

Extrinsic controls on turbidity fan lobes spatial distribution and potential reservoir presence prediction in half-graben lacustrine basin during early syn-rift: Insights from stratigraphic forward modelling - Bingyi Chen; Peter M. Burgess; Chengyan Lin; Lihua Ren; Chunmei Dong; Zheng Cao (Marine and Petroleum Geology, 2023)

The characteristics and origin of chlorite coats in the Oligocene gas sandstone reservoirs of the Upper Huagang Formation, Xihu Depression, East China Sea Shelf Basin - Jianli Lin; Chengyan Lin; Pengjie Ma; Chunmei Dong; Binbin Liu; Xin Huang; Xianguo Zhang; Xiaohan Zhao (Sedimentary Geology, 2023)

Evaluation of policy synergy in coastal ocean pollution prevention and control: The case from China - Chengyan Yao; Mengge Sun; Lin Liu (Frontiers in Marine Science, 2023)
In recent years, the Chinese central government and coastal provincial governments have promulgated a series of Coastal Ocean Pollution Prevention and Control Programs (COPPCP). Whether the government’s COPPCP can achieve policy synergy will affect the level of marine pollution governance. This study constructs a two-dimensional assessment framework of policy “subject department”–”content theme” and conducts a comprehensive evolution of policy synergy from objective, process, and state perspectives. From the subject department dimension, the study used social network analysis to find that interdepartmental collaboration was not done well overall. The policy synergy process is difficult to be guaranteed. Meanwhile, the structure of departmental synergy networks in different provinces shows differences and can be divided into three types of governments with single-core, multi-core, and vertical synergy. In the content synergy dimension, it was found by the Chinese Bidirectional Encoder Representations from Transformers-Whole Word Masking (BERT-WWM) model that the policy content is mainly focused on four themes of marine ecological protection (MEP), marine pollution control (MPC), land-based pollution reduction (LPR), and safeguard measures (SAM). The three types of governments show different performances on the four theme synergies. The governments perform well in the objective synergy; however, it is difficult for them to agree on the policy tool synergy, and the status of policy synergy is difficult to maintain. This paper adopts the BERT-WWM model instead of the manual coding method in the previous policy content analysis, enhancing the evaluation’s objectivity. The study results will provide a reference for further improving marine pollution governance systems in developing countries.

Effect of faulting on diagenetic processes in the silicate-sulfate-carbonate system: A case study from the Bonan Sag of Jiyang Depression, Bohai Bay Basin - Pengjie Ma; Chengyan Lin; Chunmei Dong; Lihua Ren; Jens Jahren; Helge Hellevang; Jianli Lin (Marine and Petroleum Geology, 2023)

Synthesis, Characterization of NR@SiO2/PNIPAm-co-Ppa Composite Nanogel and Study On Its Application in Photodynamic Therapy - Zirui Wang; Qiusheng Song; Lin Zhu; Chengyan Zhao; Haihong Ma (Journal of Fluorescence, 2022)

Stem-Cell Therapy as a Potential Strategy for Radiation-Induced Brain Injury - Chengyan Chu; Yue Gao; Xiaoyan Lan; Jianwen Lin; Aline M. Thomas; Shen Li (Stem Cell Reviews and Reports, 2020)

Quantitative Relationship Between Argillaceous Caprock Thickness and Maximum Sealed Hydrocarbon Column Height - Cunfei Ma; Chengyan Lin; Chunmei Dong; Guoqiang Luan; Yu Zhang; Xiaolong Sun; Xiaocen Liu (Natural Resources Research, 2020)

Acceleration of thaw slump during 1997–2017 in the Qilian Mountains of the northern Qinghai-Tibetan plateau - Cuicui Mu; Jianguo Shang; Tingjun Zhang; Chengyan Fan; Shufa Wang; Xiaoqing Peng; Wen Zhong; Feng Zhang; Mei Mu; Lin Jia (Landslides, 2020)

Impacts of High-Frequency Atmospheric Forcing on Southern Ocean Circulation and Antarctic Sea Ice - Yang Wu; Zhaomin Wang; Chengyan Liu; Xia Lin (Advances in Atmospheric Sciences, 2020)

Whole-genome mining and in silico analysis of FAD gene family in Brassica juncea - Yufei Xue; Chengyan Chai; Baojun Chen; Xiaofeng Shi; Bitao Wang; Fanrong Mei; Manlin Jiang; Xueli Liao; Xia Yang; Chenglong Yuan; Lin Zhang; Yourong Chai (Journal of Plant Biochemistry and Biotechnology, 2020)

Pore size distribution and reservoir characterization: evaluation for the Eocene beach-bar sequence, Dongying Depression, China - Muhammad Aleem Zahid; Dong Chunmei; Alexandra N. Golab; Chengyan Lin; Xianguo Zhang; Xinmin Ge; Wu Songtao; Muhammad Jawad Munawar; Cunfei Ma; Lydia Knuefing (Arabian Journal of Geosciences, 2019)

Sedimentological characteristics and controlling factors on fluvial styles of the Guantao Formation, Kongdian Oilfield, China - Hai Liu; Chengyan Lin; Xianguo Zhang; Hongwei Wang; Xiaoliang Fu (Journal of Earth System Science, 2019)

Paleogeomorphology restoration and the controlling effects of paleogeomorphology on karst reservoirs: a case study of an ordovician-aged section in Tahe oilfield, Tarim Basin, China - Changcheng Han; Chengyan Lin; Ting Wei; Chunmei Dong; Lihua Ren; Xianguo Zhang; Li Dong; Xu Zhao (Carbonates and Evaporites, 2019)

Impacts of open-ocean deep convection in the Weddell Sea on coastal and bottom water temperature - Zhaomin Wang; Yang Wu; Xia Lin; Chengyan Liu; Zelin Xie (Climate Dynamics, 2017)

Seismic sedimentology interpretation method of meandering fluvial reservoir: From model to real data - Tao Zhang; Xianguo Zhang; Chengyan Lin; Jingfeng Yu; Shouxiu Zhang (Journal of Earth Science, 2015)

Seismic sedimentology and its application in shallow sea area, gentle slope belt of Chengning uplift - Xianguo Zhang; Chengyan Lin; Tao Zhang (Journal of Earth Science, 2010)